AS AN INTERVENING VARIABLE JOB SATISFACTION AND ORGANIZATION COMMITMENT TO TURN OVER REWARD EMPLOYEES IN ISLAMIC BANKING IN THE BATAM, INDONESIA - Wibisono, Chablullah; Zulva Adi, Ahmad (IJRDO - Journal of Applied Management Science, 2017)
he high rate of employee turnover leads to adverse effects to an organization. Such problem is Likely generating instability and uncertainty towards employment condition and human resources cost rise in forms of training invested in them, recruitment and newly built training programs. High employee turnover, in addition, results in organizational ineffectiveness Also Because It loses experienced employees as well as spends many times in training new, inexperienced employees. This study aims to analyze the effect of organizational commitment, turnover intention to reward through work satisfaction variables and to analyze the most effective variables on turnover intention. According to the analysis, it is concluded as the followings: organizational commitment has effect on work satisfaction, reward has effects on work satisfaction,